Physical disabilities caused by leprosy in 100 million cohort in Brazil - Sanchez, Mauro Niskier (BMC Infect Dis, 2021)
BACKGROUND: Leprosy continues to be an important cause of physical disability in endemic countries such as Brazil. Knowledge of determinants of these events may lead to better control measures and targeted interventions to mitigate its impact on affected individuals. This study investigated such factors among the most vulnerable portion of the Brazilian population. METHODS: A large cohort was built from secondary data originated from a national registry of applicants to social benefit programs, covering the period 2001–2015, including over 114 million individuals. Data were linked to the leprosy notification system utilizing data from 2007 until 2014. Descriptive and bivariate analyses lead to a multivariate analysis using a multinomial logistic regression model with cluster-robust standard errors. Associations were reported as Odds Ratios with their respective 95% confidence intervals. RESULTS: Among the original cohort members 21,565 new leprosy cases were identified between 2007 and 2014. Most of the cases (63.1%) had grade zero disability. Grades 1 and 2 represented 21 and 6%, respectively. Factors associated with increasing odds of grades 1 and 2 disability were age over 15 years old (ORs 2.39 and 1.95, respectively), less schooling (with a clear dose response effect) and being a multibacillary patient (ORs 3.5 and 8.22). Protective factors for both grades were being female (ORs 0.81 and 0.61) and living in a high incidence municipality (ORs 0.85 and 0.67). CONCLUSIONS: The findings suggest that the developing of physical disabilities remains a public health problem which increases the burden of leprosy, mainly for those with severe clinical features and worse socioeconomic conditions. Early diagnosis is paramount to decrease the incidence of leprosy-related disability and our study points to the need for strengthening control actions in non-endemic areas in Brazil, where cases may be missed when presented at early stages in disease. Both actions are needed, to benefit patients and to achieve the WHO goal in reducing physical disabilities among new cases of leprosy.